2002
DOI: 10.1079/phn2002372
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of dietary intakes of micro- and macronutrients in rural, suburban and urban populations in Costa Rica

Abstract: Objective: To compare, along with behavioural habits, the potential atherogenicity of diets in rural and urban areas in Costa Rica. Design: Subjects ðn ¼ 503Þ were randomly selected from the general population in Costa Rica. A validated food-frequency questionnaire that inquired about dietary intake in the previous year was administered once to each subject. Each subject provided plasma and an adipose tissue biopsy, which were used as biomarkers for carotenoid, tocopherol and/or fatty acid intakes. Each subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 21 publications
3
21
0
3
Order By: Relevance
“…Longitudinal studies, for example, have found associations between cognitive decline and high levels of traffic-related air pollution (Power et al, 2011) or lead in the area of residence (Shih et al, 2006;Weisskopf et al, 2007), as well as long term exposure to particulate matter (Pedata et al, 2014;Weuve et al, 2012), which are more frequent in urban areas. Other studies suggest better dietary habits for rural dwellers (Huot et al, 2004;Kabagambe et al, 2002;Kun et al, 2013;Morgan et al, 2000;Santos et al, 2014;Scarmeas et al, 2014), with important implications for cognition considering that diet is associated with active lifestyles, cardiovascular health and cognitive benefits in older age (Otaegui-Arrazola et al, 2014;Spencer, 2008), as well as involved in mediating the association between vitamin D deficiency and cognitive decline (Buell et al, 2009;Llewellyn et al, 2010;Miller, 2009;Wilkins et al, 2006), especially in living areas subject to sunlight deprivation (Romero-Ortuno et al, 2011). While acknowledging the importance of air quality and diet in understanding cognitive ageing, together with the important role of biological and sociocultural intervening factors, the present work focuses on physical characteristics of the environment, e.g.…”
Section: Prevalence Of Dementia In Rural Vs Urban Areasmentioning
confidence: 98%
“…Longitudinal studies, for example, have found associations between cognitive decline and high levels of traffic-related air pollution (Power et al, 2011) or lead in the area of residence (Shih et al, 2006;Weisskopf et al, 2007), as well as long term exposure to particulate matter (Pedata et al, 2014;Weuve et al, 2012), which are more frequent in urban areas. Other studies suggest better dietary habits for rural dwellers (Huot et al, 2004;Kabagambe et al, 2002;Kun et al, 2013;Morgan et al, 2000;Santos et al, 2014;Scarmeas et al, 2014), with important implications for cognition considering that diet is associated with active lifestyles, cardiovascular health and cognitive benefits in older age (Otaegui-Arrazola et al, 2014;Spencer, 2008), as well as involved in mediating the association between vitamin D deficiency and cognitive decline (Buell et al, 2009;Llewellyn et al, 2010;Miller, 2009;Wilkins et al, 2006), especially in living areas subject to sunlight deprivation (Romero-Ortuno et al, 2011). While acknowledging the importance of air quality and diet in understanding cognitive ageing, together with the important role of biological and sociocultural intervening factors, the present work focuses on physical characteristics of the environment, e.g.…”
Section: Prevalence Of Dementia In Rural Vs Urban Areasmentioning
confidence: 98%
“…A staple dietary pattern that included white rice and beans was identified in Costa Rican adults (12). Whereas white rice represents the main source of energy in Costa Ricans (13,14), and beans are a major source of protein, the intake of beans has been declining with urbanization (15). Because the prevalence of diabetes is increasing worldwide (16), with a 140% increase expected by 2025 in Costa Rica (17), it is imperative to understand the potential contrasting effects of white rice and beans on risk factors for diabetes, such as the metabolic syndrome, especially in populations with substantial consumption of both foods.…”
Section: Introductionmentioning
confidence: 99%
“…Σε ότι αφορά όμως την επίδραση του τόπου διαμονής στη σωματική δραστηριότητα, στη σωματική επάρκεια και στην αναπνευστική λειτουργία παιδιών, τα αποτελέσματα των μέχρι τώρα μελετών είναι αντικρουόμενα. Συγκεκριμένα, σχετικά με την επίδραση του τόπου διαμονής στα επίπεδα σωματικής δραστηριότητας των παιδιών, κάποιες μελέτες βρήκαν υπεροχή των παιδιών από αστικές περιοχές (Kristjansdottir & Vilhjalmsson, 2001;Parks, Housemann, & Brownson, 2003;Taks et al, 1991;Wilcox, Castro Housemann, & Brownson, 2000), άλλες βρήκαν υπεροχή των παιδιών από μη αστικές περιοχές (Carroll, Hostetter, & Eastman, 1996;Dollman et al, 2002;Eastman, Hostetter, & Carroll, 1992;Kabagambe, Baylin, Siles, & Campos, 2002;Ozdirenc, Ozcan, Akin, & Gelecek, 2005;Proctor et al, 1996), ενώ υπάρχουν και μελέτες που δεν έχουν βρει διαφορές μεταξύ παιδιών από αστικές και μη αστικές περιοχές (Booth, Okely, Chey, Bauman, & Macaskill, 2002;McMurray, Harrell, Bangdiwala, & Deng, 1999;Tognarelli et al, 2004). Επίσης, σχετικά με την επίδραση του τόπου διαμονής στα επίπεδα σωματικής επάρκειας των παιδιών, κάποιες μελέτες βρήκαν υπεροχή των παιδιών από αστικές περιοχές (McMurray, Harrell, Bangdiwala, & Gangsky, 1995;McNaughton, Morgan, Smith, & Hannan, 1996;Sunnegardh, Bratteby, & Sjodin, 1985;Wolanski, 1985), άλλες βρήκαν υπεροχή των παιδιών από μη αστικές περιοχές (Corlett & Mokgwathi, 1987;Ewing, Watkins, & Farrally, 1982;Watkins, Farrally, & Ewing, 1981;Wilczewski, Sklad, Krawczyk, Saczuk, & Majle, 1996), ενώ υπάρχουν και μελέτες που δεν έχουν βρει διαφορές μεταξύ παιδιών από αστικές και μη αστικές περιοχές (Booth, Okely et al, 1999;Krombholz, 1997).…”
Section: εισαγωγηunclassified
“…Συγκεκριμένα, οι Yogi et al, (1976) (Kristjansdottir & Vilhjalmsson, 2001;Parks et al, 2003;Taks et al, 1991;Wilcox et al, 2000). Από την άλλη, υπάρχουν άλλες μελέτες που είτε αναφέρουν αντίθετα αποτελέσματα (Carroll et al, 1996;Dollman et al, 2002;Eastman et al, 1992;Kabagambe et al, 2002;Ozdirenc et al, 2005;Proctor et al, 1996;Raudsepp & Pall, 1999;Sobngwi et al, 2002), είτε δεν βρίσκουν διαφορές μεταξύ αστικών και μη αστικών περιοχών (Booth et al, 2002;McMurray et al, 1999;Tognarelli et al, 2004). Στην υπεροχή των μη αστικών περιοχών αναφορικά με τη συμμετοχή σε φυσικές δραστηριότητες συνηγορεί μια σειρά μελετών.…”
Section: τόπος διαμονής και βιολογική ωρίμανσηunclassified
See 1 more Smart Citation